Hubungan Tata Letak Dapur (Kitchen Layout) Terhadap Produktivitas Kerja Karyawan Di Senja Cafe & Resto - Rasman; Hartati; Yayuk Astuti; Yusrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between kitchen layout and the level of employee work productivity at Senja Café & Resto. The research is motivated by the importance of kitchen spatial design in supporting the smooth operation of restaurant activities. Inappropriate space arrangement, inefficient equipment placement, and unstructured workflow have the potential to hinder performance and increase employees’ physical workload.This study employed a quantitative approach with a correlational research design to determine the relationship between kitchen layout as the primary factor under investigation and employee productivity as the observed outcome. Data were collected through questionnaires and direct observation involving all 15 kitchen employees. After the research instruments were confirmed to be valid and reliable, the data were analyzed using descriptive statistics and the Spearman Rank correlation test.The findings reveal a positive and significant relationship between a well-organized kitchen layout and increased employee productivity. An ergonomic kitchen design, balanced distances between work areas, and a well-structured workflow were proven to help accelerate task completion, reduce fatigue, and create a more comfortable working environment. Conversely, poorly planned layouts and limited movement space may decrease employee work effectiveness.Therefore, improving the kitchen layout can serve as an effective strategy for management to enhance operational efficiency, speed up customer service processes, and strengthen business competitiveness. Furthermore, this study is expected to serve as a practical reference for medium-scale culinary businesses in managing kitchens in a more structured, efficient, and ergonomically oriented manner. Keywords: kitchen layout, work productivity, ergonomics, employees, culinary business.